Results of Rain Observations Made in New South Wales during 1878 - Government Astronomer for New South Wales (Thomas RichardsGovernment Printer, 1879)
General results of rainfall observations in New South Wales during the year 1878 s. 5-7.
H. C. Russel ; B. A. ; F. R. A. S. ; Government Astronomer for New South Wales ; J. Tayler ; J. A. C. Willis. ; Thomas Richards.
Keywords: Opady; Australia; Kartografia; mapy; Nowa Południowa Walia (Australia); w kartografii